1999
DOI: 10.1128/mcb.19.1.251
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP A1 Recruited to an Exon In Vivo Can Function as an Exon Splicing Silencer

Abstract: Some exons contain exon splicing silencers. Their activity is frequently balanced by that of splicing enhancers, and this is important to ensure correct relative levels of alternatively spliced mRNAs. Using an immunoprecipitation and UV-cross-linking assay, we show that RNA molecules containing splicing silencers from the human immunodeficiency virus type 1 tat exon 2 or the human fibroblast growth factor receptor 2 K-SAM exon bind to hnRNP A1 in HeLa cell nuclear extracts better than the corresponding RNA mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
173
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 58 publications
(75 reference statements)
5
173
1
1
Order By: Relevance
“…In transcript C3, the second exon (positions 5359 -5408) contained the identified cis inhibitory element ESS2p that binds hnRNP H (11). However, the downstream ESS2 inhibitory element (7-9), which binds hnRNP A1 (14,16), and the recently described ESE2 activator element (41) were not present in this transcript (Fig. 1A).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In transcript C3, the second exon (positions 5359 -5408) contained the identified cis inhibitory element ESS2p that binds hnRNP H (11). However, the downstream ESS2 inhibitory element (7-9), which binds hnRNP A1 (14,16), and the recently described ESE2 activator element (41) were not present in this transcript (Fig. 1A).…”
Section: Resultsmentioning
confidence: 98%
“…(iii) Their accessibility is limited by their sequestering in stable secondary structures (24). (iv) Several cis-inhibitory elements have been identified that down-regulate the A2, A3, and A7 sites by binding of hnRNP A1 or hnRNP H proteins (11,12,14,16,18,19,21). Despite these numerous handicaps, the utilization of several of the HIV-1 acceptor sites is essential for virus multiplication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the increase in exon 7 inclusion was a specific consequence of attaching the GGA repeat sequence to SMN2 exon 7, we tested other tailed oligonucleotides that lacked ESE sequences but would anneal to the same target site. In these oligonucleotides (called 5ЈPTB and 5ЈA1), the ESE sequences were replaced with sequences that bind to inhibitors of splicing such as PTB or hnRNP A1, respectively (24)(25)(26)(27). In contrast to the 5ЈGGA oligonucleotide, both these oligonucleotides and the NT oligonucleotide demonstrated that annealing at the 5Ј end of SMN2 exon 7 was insufficient to stimulate incorporation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two hnRNP proteins frequently overexpressed in cancer-hnRNP A1 and PTB-have been implicated in silencing of the epithelial-specific IIIb exon, while hnRNP H/F proteins can contribute to IIIc silencing (Del Gatto-Konczak et al 1999;Carstens et al 2000;Mauger et al 2008). There is currently no strong evidence to suggest that changes in the levels of these hnRNP proteins provide an important means of regulating switching from exon IIIb to IIIc.…”
Section: Fgfrsmentioning
confidence: 97%